Aspects of the theory of tariffs - Johnson, Harry G. (London : Allen and Unwin, 1971)
This book has its origins in a series of five lectures on the theory of tariffs that the author was invited by the late Professor Ely Devons to offer at the London school of Economics and political science in 1964. The five lectures dealt respectively with the standard theory of tariffs, the arguments for protection, the theory of tariff structure, and tariffs and economic development
Includes bibliographical references.
osc 23/05/2018
Loans
Keywords: Tariff